Accumulation Heavy Metal on Shrimp White (Litopenaeus Vannamei) at the River Mouth of Ketahun, North Bengkulu - Rinda Fitri Handayani; Bhakti Karyadi; Deni Parlindungan; Nirwana; Fidia Fibriana (Sainmatika: Jurnal Ilmiah Matematika dan Ilmu Pengetahuan Alam, 2024)
Heavy metals are poisonous materials capable of causing damage to the normal aquatic organisms in the community around the Ketahun River estuary. The entry of heavy metals into the waters of the Ketahun River estuary is allegedly from various activities such as bathing, washing, toilet use, palm oil plantations, coal mining, and the disposal of gold mine waste. This is the background for conducting research to analyze the content of Hg, Cd, Pb, and As in Litopenaeus vannamei in the Ketahun River estuary. The determination of sampling locations was done using a purposive method, and the samples were tested using Inductively Coupled Plasma Mass Spectrometry (ICP-MS). The ecology of the river estuary was measured using a thermometer, pH meter, Dissolved Oxygen Meter, and Total Dissolved Solid Meter. The research results were analyzed using a descriptive qualitative method. According to the findings of the study, the metal content in Litopenaeus vannamei exceeds the quality standard with an analysis result of 0.2328 mg/kg, while the quality standard is 0.20 mg/kg, which has health implications. For sediment, the heavy metal that exceeds the quality standard is mercury at 0.5921 mg/kg, while the quality standard is 0.15 mg/kg. The ecology of the river estuary continues to be an ideal environment for living biota.